2021
DOI: 10.1007/s00264-021-05139-6
|View full text |Cite
|
Sign up to set email alerts
|

Does ipsilateral chronic ankle instability alter kinematics of the other joints of the lower extremities: a biomechanical study

Abstract: Purpose We evaluated and compared kinematics of bilateral ankle, knee, and hip joints in patients with chronic unilateral ankle instability (CAI) with healthy controls. Methods Fifteen individuals diagnosed with CAI and a control group of 16 individuals were matched. Different peaks within the gait cycle (at different intervals) for the dorsiplantar, inversion/eversion, and abduction/adduction axis were compared between injured and uninjured sides of patients with CAI with a control group. Results Comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Notably, our results revealed that the ipsilateral sensorimotor network was more activated in CAI patients, probably due to the compensation of the unaffected ankle (left ankle). Some studies have found that CAI patients transformed their gait and posture to compensate for the injured ankle (Levin et al, 2015;Ziabari et al, 2021), which implied reassignment of cerebral function. Under physiological conditions, the two hemispheres are mutually inhibited, but the inhibition can be upset in certain circumstances, and cerebral function can be redistributed (Zhang J. et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our results revealed that the ipsilateral sensorimotor network was more activated in CAI patients, probably due to the compensation of the unaffected ankle (left ankle). Some studies have found that CAI patients transformed their gait and posture to compensate for the injured ankle (Levin et al, 2015;Ziabari et al, 2021), which implied reassignment of cerebral function. Under physiological conditions, the two hemispheres are mutually inhibited, but the inhibition can be upset in certain circumstances, and cerebral function can be redistributed (Zhang J. et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The AJFAT-C results are based on a comparison of the affected side with the contralateral limb. However, recent studies have shown that patients with unilateral ankle instability also depict some degree of ankle dysfunction in the other limb compared to healthy individuals [ 37 39 ], which could potentially be a limiting factor in the practical application of the AJFAT-C. Additionally, during the cross-cultural adaptation of the AJFAT-C, the healthy college students reported that some of the questions in the scale were not easy to answer for respondents without a history of ankle sprain. This highlights, that the practical application of the AJFAT-C is limited to patients with a history of ankle sprain and is not recommended for assessment ankle stability in healthy subjects.…”
Section: Limitationmentioning
confidence: 99%
“…A study showed that 45% of ankle sprains in basketball players occur during landing [ 15 ]. Given that the lower limbs operate as an integrated entity, changes in a joint’s movement pattern invariably trigger modifications in the neighboring joints [ 16 ]. Theisen et al [ 17 ] reported that patients with chronic ankle instability have reduced knee flexion angles compared with the healthy control group, implying a higher risk of anterior cruciate ligament (ACL) injury.…”
Section: Introductionmentioning
confidence: 99%